Hubungan Pengetahuan, Status Gizi, Dan Peran Tenaga Kesehatan Terhadap Perilaku Pencegahan Pneumonia Pada Balita Usia 0-5 Tahun Di PMB S Belitung Timur : The Relationship between Knowledge, Nutritional Status, and the Role of Health Workers on Pneumonia Prevention Behavior in Toddlers Aged 0-5 Years in PMB S East Belitung - Inda, Viranti Monata (Dohara POAJ, 2024)
Introduction: Pneumonia is a major health problem in Indonesia because the incidence of pneumonia is still high, especially in children. The World Health Organization (WHO) stated that pneumonia killed 740,180 children aged 1 to 5 years in 2019 or 36% of all child deaths in the world. Methods: The research design uses quantitative research with analytical descriptive research and uses a cross-sectional design where the research is carried out when collecting data between the independent variable and the dependent variable which is carried out together at the same time. The sampling technique used in this research was a total sampling of 57 study respondents, population, sample, place and time of research, data collection procedures and tests used. Results: Good knowledge with positive behavior as many as 25 respondents (73,5%) respondents had normal nutritional status with positive behavior as many as 25 respondents (96,2%) 24 respondents (72,7%) played a role in health workers who had positive behavior. There is a relationship between knowledge, nutritional status and the role of health workers in pneumonia prevention behavior in toddlers aged 0-5 years in PMB S East Belitung in 2023. Discussion: With this research it is hoped that mothers can understand the health of their toddlers.